A tale of two narratives: student voice—what lies before us?. (4th March 2017) - Hall, Valerie
Abstract: As the last century closed, and a bright new millennium dawned, the concept of 'student voice' within education emerged as something to be ' identified ' and ' captured '. In effect, it became reified and driven by a raft of government and institutional policies and strategic initiatives; initially within the compulsory sector, but soon followed by the post-compulsory sector as the 2000s moved on. In an increasingly quasi-consumerist environment, a mechanism had emerged with potential to ' measure ' student satisfaction. Institutions quickly took up the 'call to arms', assigning responsibilities to ensure there was evidence of 'student voice' engagement; but there was no conversation with the 'students' about how this was experienced by them. This concept had become a 'portmanteau' term; a 'catch all' competing between two narratives—student voice as democratic and transformational; and student voice as 'policy' and strategic initiative. Formal research that could contribute to this discussion has been sparse and this paper takes a critical stance to the literature and policy, exploring the current status of student voice and proposing a research focus that has the potential to involve students in a discussion about how their voice is heard, and for what purpose.